The Effect of Internal Audit and Wishtleblowing System on Fraud prevention at PT. PLN (Persero) UP3 Binjai - Windi Ayuni, Tyus; Hou, Amin; Razaq, Mhd Restu (Journal of Finance Integration and Business Independence, 2024)
This study aims to analyze the effect of internal audit and whistleblowing system on fraud prevention in PT. PLN (Persero) UP3 Binjai. Fraud is a serious problem that can harm a company financially and reputationally. The method used in this study is a quantitative approach with data collection through questionnaires distributed to employees at PT. PLN (Persero) UP3 Binjai. Data analysis was performed using multiple linear regression to test the hypothesis.The results showed that internal audits have a positive and significant effect on fraud prevention, which means that the better the implementation of internal audits, the lower the likelihood of fraud. In addition, the whistleblowing system is also proven to contribute to fraud prevention by providing a channel for employees to report fraudulent actions without fear of retaliation. The study concluded that the combination of an effective internal audit and a good whistleblowing system can significantly reduce the risk of fraud in the company